Tooth Supported Maxillary Overdenture: A Treatment Modality Overshadowed but Still Not Omitted-A Case Report - Singh, Somika Kumari (Journal of College of Medical Sciences-Nepal, 2025)
Background The concept of overdentures developed as a simple, time saving and cost-effective alternative to prolong the retention, stability and function of the last few remaining teeth in a compromised dentition. Tooth supported overdentures are more stable, retentive and patients can chew greater than conventional complete dentures. Case A 70-year-old female patient reported to the Department of Prosthodontics and Crown-Bridge, BPKIHS, Dharan for prosthetic rehabilitation of maxillary and mandibular edentulous ridges. Intra oral examination revealed, completely edentulous lower arch and 11, 21 and 22 teeth were present in upper arch. Treatment plan was made to rehabilitate tooth supported maxillary overdenture prosthesis and conventional mandibular denture. Conclusion Tooth supported overdenture has many advantages over implant supported prosthesis such as, simple, economical, time saving, preserve tooth structure and alveolar bone, provide retentive and stable prosthesis, preserve proprioception, patient psychological benefits. So, now a day this treatment modality overshadowed but still not omitted.